Analisis perbandingan rencana strategis antar perbankan syariah: Studi kasus pada Bank Bukopin Syariah, Bank Victoria Syariah, Bank Panin Dubai Syariah - Mustaqfiroh, Novi Kholifatul; Sonia, Lailatul Izzah; Hidayah, Nurul (Maliki Interdisciplinary Journal, 2023)
Banks are commercial institutions that collect people's money for savings and distribute it to the community through credit and/or other means to improve the standard of living of many people. People's banking services are divided into two categories: traditional banking services and sharia banking services. Strategic management is an ongoing set of activities and processes that organizations use to systematically coordinate and align resources and actions based on their mission, vision, and strategy. This research aims to determine the differences in strategic plans owned by Bank Bukopin Syariah, Bank Victoria Syariah and Bank Panin Dubai Syariah. This research uses a qualitative descriptive method with a literature review type. This research found differences in the strategic plans of the three Islamic banks both long term, short term and in SWOT analysis.